Mobilizing for Elections: Patronage and Political Machines in Southeast Asia. Edward Aspinall, Meredith L. Weiss, Allen Hicken & Paul D. Hutchcroft. - Yoshinori Nishizaki (Taylor & Francis, 2024)
10.1080/03068374.2023.2278966